A cohort analysis of the income distribution in Chile - Sapelli, Claudio (Estudios de Economía, 2016)
In this paper we look at the income distribution by cohort in Chile. We construct a synthetic panel from cross section surveys and estimate the income distribution for cohorts born between 1902 and 1978. We then decompose the evolution of these distributions into age, year and cohort effects. The cohort effects show a period where inequality increases, to then decrease. We attempt to explain this evolution. The rise can be explained by variables associated with education, while the fall appears to be the consequence of a flattening of the income-age profile and hence a reduction in the returns to experience.